2007
DOI: 10.1104/pp.107.104851
|View full text |Cite
|
Sign up to set email alerts
|

A Central Role of Abscisic Acid in Drought Stress Protection of Agrobacterium-Induced Tumors on Arabidopsis

Abstract: Crown gall tumors induced by Agrobacterium tumefaciens represent a sink that has to be provided with nutrients and water by the host plant. The lack of an intact epidermis or cuticle results in uncontrolled loss of water. However, neither the tumor nor the host plant displays wilting. This phenomenon points to drought adaptation in both tumors and the crown gall host plant. To understand the underlying molecular mechanisms of protection against desiccation the gene expression pattern of Arabidopsis (Arabidopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
69
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 66 publications
(89 reference statements)
4
69
0
Order By: Relevance
“…For example, two desaturases, the stearoyl-acyl carrier protein desaturase SAD6 and the fatty acid desaturase FAD3, are highly expressed and enrich the unsaturated fatty acid pool, which helps in maintaining membrane integrity (Klinkenberg et al, 2014). Second, a suberin-containing periderm-like layer covers the surface of crown galls to minimize water loss and avoid pathogen invasion (Efetova et al, 2007).…”
mentioning
confidence: 99%
“…For example, two desaturases, the stearoyl-acyl carrier protein desaturase SAD6 and the fatty acid desaturase FAD3, are highly expressed and enrich the unsaturated fatty acid pool, which helps in maintaining membrane integrity (Klinkenberg et al, 2014). Second, a suberin-containing periderm-like layer covers the surface of crown galls to minimize water loss and avoid pathogen invasion (Efetova et al, 2007).…”
mentioning
confidence: 99%
“…These differences revealed that the host responded to both agrobacterial strains as early as 3 h postinoculation and that the oncogenic strain C58 incites a much stronger pathogen defense response than strain GV3101 at both early time points. Furthermore, our studies documented that the development of Agrobacterium-induced tumors on Arabidopsis was accompanied by elevated production of abscisic acid (ABA) (Efetova et al, 2007), IAA, SA, and ET, but not JA. This was in agreement with previous findings that the development of Agrobacterium-induced tumors on Ricinus communis involves the production of the phytohormones JA, auxin, cytokinin, ET, and ABA (Veselov et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…For successful tumor development, morphological adaptations are essential: these include neovascularization to supply the growing tumor with nutrients (Ullrich and Aloni, 2000) and suberization of the outer cell layers to protect the disrupted tumor surface against drought stress (Efetova et al, 2007). Hydrogen peroxide production in fully developed tumors ( Figure 1H) and the expression of 34 genes involved in oxidative stress ( Figure 4B) are at least partly associated with suberization of outer tumor cell layers.…”
Section: Auxin and Et Are Involved In The Initiation Of Infection Witmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA may enable Euglena gracilis cells in culture to mitigate abiotic and/or biotic stress conditions developing in vitro, thereby producing high cell concentrations, similar to beneficial effects on Arabidopsis plants of inoculation with ABA-producing bacteria under stress conditions (Cohen et al, 2008). In Euglena, ABA may play a promotive role and enhance growth, as in vascular plant systems where ABA is not only a hormone that regulates stress-signalling and controls stress responses, but often is critical for seed filling and tumour development (Efetova et al, 2007;Tuteja, 2007;Santner et al, 2009). Euglena gracilis cultures showed a significant increase in cell numbers in response to exogenous CKs, tZ, iP and BAP at their optimal concentrations.…”
Section: Discussionmentioning
confidence: 99%